BUSINESS PLAN : RENCANA PENDIRIAN EVENT ORGANIZER - Sazili, Zidhan Asy; Hussein, Ananda Sabil (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Opportunities for business services for organizing activities that are increasingly widespread and developing, either as activity planners or activity organizers. Here preparations that must be made to conduct events such as community gathering, music concert, wedding, and corporate events are discussed. The objective of this study is to determine strategies that will be realized based on the analyses on the related aspects in order to develop and to face competition in event organizing business in Bojonegoro. This qualitative descriptive research uses primary data obtained from observations and interviews and secondary data compiled from relevant literature. This study finds that the business planning has met the necessary aspects such as analysis of customer’s interest, support from the government, the availability of other companies for partnership purposes, planning workflow and event execution, analyses on competitors of the same field of industry, required service variations, form of partnership agreements, business legality, and analyses of sponsors from other companies as the supporting parties for the organization of an event.